2021 IEEE 18th International Symposium on Biomedical Imaging (ISBI) 2021
DOI: 10.1109/isbi48211.2021.9433826
|View full text |Cite
|
Sign up to set email alerts
|

Dense Pixel-Labeling For Reverse-Transfer And Diagnostic Learning On Lung Ultrasound For Covid-19 And Pneumonia Detection

Abstract: We propose using a pre-trained segmentation model to perform diagnostic classification in order to achieve better generalization and interpretability, terming the technique reverse-transfer learning. We present an architecture to convert segmentation models to classification models. We compare and contrast dense vs sparse segmentation labeling and study its impact on diagnostic classification. We compare the performance of U-Net trained with dense and sparse labels to segment A-lines, B-lines, and Pleural line… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
23
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(24 citation statements)
references
References 13 publications
0
23
0
Order By: Relevance
“…In addition, we compared our method with two main detection methods using the same LUS testing set, including the equidistance method proposed by Anantrasirichai et al 21 . and the U‐Net detection method proposed by Gare et al 30 . Their detection accuracies all were evaluated using the “depth” index introduced in Section 2.3.3, whose experimental results were shown in Figure 11.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…In addition, we compared our method with two main detection methods using the same LUS testing set, including the equidistance method proposed by Anantrasirichai et al 21 . and the U‐Net detection method proposed by Gare et al 30 . Their detection accuracies all were evaluated using the “depth” index introduced in Section 2.3.3, whose experimental results were shown in Figure 11.…”
Section: Resultsmentioning
confidence: 99%
“…In other words, the final accumulated accuracy of the whole system was 93.39% and 91.90% for convex and linear probes, respectively. In addition, we compared our method with two main detection methods using the same LUS testing set, including the equidistance method proposed by Anantrasirichai et al 21 and the U-Net detection method proposed by Gare et al 30 Their detection accuracies all were evaluated using the "depth" index introduced in Section 2.3.3, whose experimental results were shown in Figure 11. The comparison results showed that our method was better than the previous classical methods on both linear array and convex array probes.…”
Section: Comparison With Other Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…They further introduced a third sampled quaternary method to annotate all frames based on only 10% positively labeled samples from the whole dataset, which outperformed the previous two labeling strategies. Gare et al tried to convert a pre-trained segmentation model into a diagnostic classifier and compared the results from dense vs. sparse segmentation labeling [ 84 ]. Tested on a restricted dataset of 152 images from four patients (three COVID-19 positives and one control), they found that with pretrained segmentation weights and dense labeling pretrained U-net, the classifier performs best with an overall accuracy of 0.84.…”
Section: Machine Learning In Covid-19 Lusmentioning
confidence: 99%
“…Related Work Current LUS AI approaches [22,3,10] train models directly for the diagnostic end task, sometimes using segmentation labels for pretraining [24,11] to help improve performance. Although segmentation labels may be thought of as a type of biomarker, segmentations do not succinctly describe the key properties of the videos and segmentation labels are costly to obtain.…”
Section: Introductionmentioning
confidence: 99%